Conceptual Model for Retention of Women Employees: A Review of Literature - Srikumar, Swapna; Shalini, P (International Journal of Psychosocial Rehabilitation, 2020)
--In India gender inequality subsists and conquers in all segments like fitness, learning, finances and political affairs. Men had constantly a higher hand in all areas, portraying how patriarchy is engrained in India. Even gender parity has improved to great elevations from post-independence age, many phases have been taken in various areas to bridge the crack between men and women. Women are behind in terms of profile and growth in companies and government areas. Various curriculums and orders have been propelled to provide equal chances for men and women. This has resulted in increase in number of job opportunities of womenfolk in various sectors. This growing tendency has led to fluctuations in firms. Previously, not a solo lady was seen in the top level of firms. Today, there has been progress in the number of females in the top levels in all firms. These subjects are very much debatable why females are still behindhand than men in spite of the surge in the amount of chances and favorable achievement curricula. The year 2017 was the year in which India’s feminine labor force involvement rates fell to its lowest since freedom. Women in the work force has revealed a drop over the last seven decades. The female labor force participation rate was at 33% in 1972-73 and showed a drop till the year 1999-2000, when it moved to 26%. It was at 17.5% in 2017-2018, and it was the lowest in the Indian history ever. This situation gifts us with a unusual puzzle – when the a country seeing substantial improvement in female education, and a notable decrease in fertility proportions, and an growing economic development with a greater sharing of women in the workforce.